Critical interpretation and analysis to correlate the canopy height to collector diameter ratio for optimized design of solar chimney power plants - Iylia Elena Abdul Jamil; Hussain H. Al-Kayiem; Sundus S. Al-Azawiey; Aseel K. Shyaa (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
The collector's periphery height determines the entrance size to the solar chimney power plant. There is inconsistency in the published experimental and numerical results on the optimum collector inlet height for different collector diameters. This paper aims to analyze the available data to identify the best collector inlet height-to-diameter ratio and to introduce a design guide for an optimized performance of solar chimney power plants. The experimental data reported in previous works have been clustered and manipulated to produce a comparative argument on the collector inlet height-to-diameter. In addition, a numerical model is developed to support the literature conclusions and to produce further data to decide the optimum collector inlet height-to-diameter ratio. For a 6.6-m collector diameter, four different inlets have been investigated, namely, 0.05, 0.1, 0.15, and 0.2 m. The best performance in terms of air velocity and temperature rise is obtained with the 0.05-m inlet height, where it shows an improvement of up to 35.35% compared to the larger inlet heights. The lower collector inlet height allows a more effective heat transfer from the ground and the collector to the air. It is concluded that the optimum collector inlet height-to-diameter design ratio for solar chimneys with collector diameters larger than 3 m is 0.0075±0.0005. For small-scale solar chimney models with less than 3 m collector diameter, the best collector inlet height-to-diameter ratio ranges between 0.015 and 0.03.